CHEMICAL CHARACTERISTICS OF PROCESSED SUI WU'U PORK PRESERVED WITH ADDITION OF CORN FLOUR IN DIFFERENT CONCENTRATIONS - N K.D., Maharani; Miwada, I N. S.; Lindawati, S. A. (Jurnal Peternakan Tropika; Vol 9 No 2 (2021): Vol. 9 No. 2 Tahun 2021; May - August, 2021)
This study aims to find out the chemical characteristics of processed sui wu'u pork preserved with addition of corn flour in different concentrations. This research was conducted at the Laboratory of Animal Product Technology & Microbiology and Laboratory of Animal Nutrition and Feed Faculty of Animal Husbandry Udayana University in September-November 2020. This study used a Completely Randomized Design (CRD) with three treatments and five replications. The three treatments: landrace pork which was preserved with the addition of 0.5 kg of corn flour (P1), landrace pork which was preserved with the addition of 1 kg of corn flour (P2), landrace pork which was preserved with the addition of 1 kg of corn flour 1.5 kg (P3). The research data were analyzed using variance (anova) and if the treatment had a significant effect, it was continued with Duncan test. The variables observed were moisture content, protein content, fat content, and ash content. The results of the chemical test of landrace pork preserved by traditional preservation of sui wu’u with the addition of different corn flour showed no significant differences, with the average moisture content (P1: 59.79%, P2: 54.99%, P3: 51.20%), protein content (P1: 19.69% P2: 22.07%, P3: 26.30%), fat content (P1: 13.37%, P2: 15.49%, P3: 17.02%), and ash content (P1: 2.63%, P2: 2.19%, P3: 2.55%). Based on the results of this study it can be concluded that the addition of different corn flour has no significant effect on the chemical quality of landrace pork so that in this study the effectiveness of using corn flour was sufficient in the P1 treatment with the addition of 0.5 kg in the sui wu'u preservation method.   Key words : chemical characteristics, pork, Sui wu’u, corn flour